To love and cherish - Peterson, Tracie (Peterson, Tracie. Bridal Veil Island, 2012)
When the love of her life, Evan, goes missing after a hurricane strikes Bridal Veil Island in 1898, Melinda Colson returns to search for him, but as she settles into a new job, and a new life, how long will she be able to hold out hope?